MULTI-FUNCTIONING HOME BOT WITH INTEGRATED FEEDBACK SYSTEM - Satapathy, Lalit Moha; Bastia, Samir Kumar; Mohanty, Nihar (APTIKOM Publisher, 2019)
Now-a-days, automation in home is becoming more popular. It always remains important to consideraccuracy and speed in a said job. This paper is addressing an Arduino Mega micro-controller based Home Bot,which has several aspects like cleaning of the floor and on-off switches as per requirement, theft detection andmonitoring. The ability of the proposed model is auto pathfinding when ever hurdles appear and auto detection whena trouble appears inside the Home Bot. It is verified that the cost of this module is around 21%, compared to therobots available in the market having features of only floor cleaning.